Application of logistic regression to assess the factors associated with HIV-related knowledge among university students - Idari Ismail; Mas Izatul Aida Abdul Aziz; Nur Amira Mohd Noor; Nur Aunie Izzati Mailin; Nur Syaliza Hanim Che Yusof (Penerbit Universiti Kebangsaan Malaysia, 2021)
Human Immunodeficiency Virus (HIV) has become a serious world's health challenge and burden. The majority of young people lack knowledge on how HIV is transmitted and how to prevent themselves from being infected. Therefore, this study was conducted to determine the knowledge level of HIV/AIDS and identify significant demographic factors that affect the knowledge level using selected statistical analysis. This cross-sectional study involved young adult university students from UiTM Cawangan Kelantan, Kampus Kota Bharu. A questionnaire that consists of demographic characteristics and HIV Knowledge Questionnaire 18 (HIV-KQ-18) was distributed to 280 respondents with a response rate of 79%. The demographic predictors examined in this study are age, gender, mother's and father's education level, monthly household income, residence area, family history of HIV and health insurance status. The dependent variable in this study is the knowledge level of HIV/AIDS that is categorised into 0 and 1; 0 denoting the low level of knowledge (score < 7) and 1 indicating a high level of knowledge (score ≥ 7). The results revealed that 68% of the respondents have high knowledge of HIV/AIDS infection. However, misconceptions about HIV transmission and its prevention still exist among the respondents. The findings from logistic regression analysis indicated that younger students (OR = 0.732) and those who lived in urban areas (OR = 1.973) were more likely to have high knowledge of HIV. The results also revealed that students who were covered with health insurance (OR = 2.913) were more likely to have high knowledge of HIV than those who are not. Thus, it is suggested that the concerned parties should aggressively educate the public through awareness-raising campaign and use the mass media to deliver information about HIV/AIDS targeting youngsters from specific age group and socio-economic status, and those who lived in rural areas.